Risk of stroke and other adverse outcomes in patients with perioperative atrial fibrillation 1 year after non-cardiac surgery. (25th June 2019) - Conen, David; Alonso-Coello, Pablo; Douketis, James; Chan, Matthew T V; Kurz, Andrea; Sigamani, Alben; Parlow, Joel L; Wang, Chew Yin; Villar, Juan C; Srinathan, Sadeesh K; Tiboni, Maria; Malaga, German; et al.
Abstract: Aims: To determine the 1-year risk of stroke and other adverse outcomes in patients with a new diagnosis of perioperative atrial fibrillation (POAF) after non-cardiac surgery. Methods and results: The PeriOperative ISchemic Evaluation (POISE)-1 trial evaluated the effects of metoprolol vs. placebo in 8351 patients, and POISE-2 compared the effect of aspirin vs. placebo, and clonidine vs. placebo in 10 010 patients. These trials included patients with, or at risk of, cardiovascular disease who were undergoing non-cardiac surgery. For the purpose of this study, we combined the POISE datasets, excluding 244 patients who were in atrial fibrillation (AF) at the time of randomization. Perioperative atrial fibrillation was defined as new AF that occurred within 30 days after surgery. Our primary outcome was the incidence of stroke at 1 year of follow-up; secondary outcomes were mortality and myocardial infarction (MI). We compared outcomes among patients with and without POAF using multivariable adjusted Cox proportional hazards models. Among 18 117 patients (mean age 69 years, 57.4% male), 404 had POAF (2.2%). The stroke incidence 1 year after surgery was 5.58 vs. 1.54 per 100 patient-years in patients with and without POAF, adjusted hazard ratio (aHR) 3.43, 95% confidence interval (CI) 2.00–5.90; P < 0.001. Patients with POAF also had an increased risk of death (incidence 31.37 vs. 9.34; aHR 2.51, 95% CI 2.01–3.14; P < 0.001) and MI (incidence 26.20 vs. 8.23; aHR 5.10, 95% CI 3.91–6.64; P < 0.001). Conclusion: Patients with POAF have a significantly increased risk of stroke, MI, and death at 1 year. Intervention studies are needed to evaluate risk reduction strategies in this high-risk population.